Limb load asymmetries in static and dynamic postural tasks: athletic training influences - Koutakis, P.; Voudouris, D.; Hatzitaki, V.; Grouios, G. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Limb load asymmetries during postural and dynamic activities such as standing up or gait are considered normal in healthy, able-bodied individuals [1]. These are attributed to several factors such as specific task constraints [2], limb dominance [3], aging, absence of vision [4] or simply individual differences [3]. On the other hand, a growing concern is the fact that sport-specific training over the years results in the development of specialized muscular synergies that generate an imbalance of the forces acting statically or dynamically at the joints leading to alterations of posture and predisposing athletes to injury [5]. The purpose of the present study was to examine whether long term specialized training of jumpers and long distance runners enhances limb load asymmetries during quiet standing and performance of a sit to stand task. Methods A group of 16 jumpers and long distance runners (mean age: 25±8 years, height: 178±16 cm, weight: 71.5±28.5 kg, years of training: 6±3.1) and 14 age-matched controls (mean age: 24.5±5.5 years, height: 176±14 cm, weight: 74±19 kg) were asked to stand on two adjacent force platforms (ERBE Balance System, sampling rate: 1000 Hz) and perform the following tasks: a) 20s of quiet standing, b) a sit to stand task (subjects were sitting upright with thighs supported half length by the seat and the shanks flexed 10o over the vertical). Both tasks were performed with eyes open (EO) and closed (EC). Performance was quantified by the mean vertical ground reaction force (Fz) depicted on each foot during the 20s of quiet standing and the force integral calculated over the push-off phase of the sit to stand task and normalized with respect to body weight. An asymmetry index (AI) in limb load distribution was then calculated based on the following relationship: (FzR-FzL /FzR+FzL)*100 [6]. Differences between the groups and task conditions (static vs. dynamic, eyes closed vs. eyes open) were analyzed by means of a 2x2x2 repeated measures ANOVA. Results Asymmetry in limb load distribution increased significantly [F(1,28) = 50.5, p<0.001] during performance of the dynamic task (36% mean difference) compared to quiet standing (6% mean difference). In addition, a significant task x group interaction [F(1,28) = 4.59, p<0.05] suggests that limb load asymmetry was significantly different between the two groups only in the dynamic task. Specifically, non-athletes exhibited a 13% greater asymmetry in weight distribution than athletes were rising from a chair (Fig.1). This difference was even greater (20%) with EC, although overall differences in limb load asymmetries due to the absence of vision were not confirmed by the statistical analysis.